Improved resin system for foamed fire-retardant coating

CN117836036BActive Publication Date: 2026-10-13ROHM GMBH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202280051682.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-08-02
Filing Date
2022-06-27
Publication Date
2026-10-13
Estimated Expiration
2042-06-27

AI Technical Summary

Technical Problem

这种工艺链相对复杂,并且对简化有很大的兴趣

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004676899220000121
    Figure BDA0004676899220000121
Patent Text Reader

Abstract

The invention relates to a novel reactive resin system for intumescent coatings and a method for producing said resin system. Intumescent coatings are used in particular for the fire protection of metal components, such as steel beams in building construction. Upon the occurrence of a fire, the coatings react to form a fireproof insulation layer with low thermal conductivity on the metal beams and delay the early heat-induced failure of the components by the resulting insulation effect. The invention relates in particular to a methacrylate-based resin system produced by means of a novel method, in which a first monomer fraction is polymerized to a maximum of 95% by weight, and then diluted with a second monomer mixture. The glass transition temperature of the polymer component of the composition formed here is particularly low compared to the prior art. Furthermore, the organic acid introduced into the resin system has a surprising synergistic effect with the filler system. The resin system produced in this way proves to be particularly effective in terms of heat-induced foaming due to its fine-pored and closed-cell foam structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a novel reactive resin system for intumescent coatings and a method for producing said resin system. Intumescent coatings are particularly suitable for fireproofing metal components, such as steel beams in building structures. In the event of a fire, the coating reacts and foams to form a fire-resistant insulating layer with low thermal conductivity on the metal beam, thereby delaying early thermal failure of the component through the resulting insulating effect.

[0002] This invention specifically relates to a methacrylate-based resin system prepared by a novel method, wherein a first monomer mixture is polymerized to a maximum extent of 95% by weight, and then diluted with a second monomer mixture. The glass transition temperature of the polymer component in the composition formed herein is particularly low compared to the prior art. Furthermore, the organic acid introduced into the resin system exhibits an unexpected synergistic effect with the filler system. The resulting resin system has proven particularly effective in thermo-induced foaming due to its fine-pore and closed-cell foam structure. Background Technology

[0003] First-generation intumescent coating systems are based on high-molecular-weight thermoplastic resins derived from acrylates, methacrylates, and / or vinyl monomers, and require a high proportion of solvent or water to be applied to the corresponding metal surfaces, resulting in correspondingly long drying times.

[0004] Such intumescent coatings are typically applied on-site during the construction phase. However, off-site application before delivery to the construction site is preferred because it can be done under controlled conditions. However, slow drying results in inefficient processing times, especially since the coating must be applied sequentially from different sides for complete coverage.

[0005] CN 112 029 367A describes, for example, an expanded system in the form of an emulsion, which contains core-shell particles in water. The core of the core-shell particles is cross-linked.

[0006] CN 111 995 919A and CA 3 028 431 both disclose emulsions of acrylic polymers in the form of ultrathin, expandable coatings. The acrylic polymer exists in the form of core-shell particles, wherein the core is cross-linked.

[0007] JP 2003 171 579 relates to a mixture of unpolymerized (meth)acrylic monomers and (meth)acrylic polymers. This mixture can be used as an intumescent coating. No polymerization termination at a specified degree of polymerization is disclosed.

[0008] DE 196 30 063 relates to interior trim components for rail vehicle assemblies. No intumescent coatings are disclosed.

[0009] Epoxy-based intumescent coatings are preferred for use in the marine industry. Their advantages lie in their good aging resistance and relatively short drying time. Polyurethane systems have been extensively studied. Their advantages also include relatively short drying time and good water resistance. However, the results of fire resistance tests were unsatisfactory due to the poor adhesion of this coating to steel. Details can be found in *Development of alternative technologies for off-site applied intumescent*, Longdon, PJ, European Commission, [Report] EUR (2005), EUR 21216, 1-141.

[0010] Another generation of intumescent coatings is based on (meth)acrylate reactive resins. Its application has a significant advantage: no solvent is required; moreover, once applied, the resin cures relatively quickly compared to the systems described above. This not only results in faster processing but also, in particular, leads to a lower content of residual volatile components in the applied coating. Such an intumescent coating system was first disclosed in EP 1636 318.

[0011] Further improvements to the (meth)acrylate-based system are subsequently described, for example, in EP 2 171 004. It is characterized by a particularly high content of acid groups to improve metal adhesion. EP 2 171 005 discloses a further development of this system. Its features are particularly evident in the copolymerization of diacids or copolymerizable acids with spacer groups. This can further improve metal adhesion.

[0012] However, all these systems require further improvement. For example, the degree of freedom in configuration is severely limited. It is also possible to apply only relatively thick layers. This combination of drawbacks also means that, for example, the foam height can only be preset to a very limited extent when needed or in case of fire.

[0013] Furthermore, the relatively complex production methods of the resin also present drawbacks. All the (meth)acrylate systems described in the prior art, which are otherwise highly advantageous, share the common feature that the solid thermoplastic polymer present in the resin is produced separately, then dissolved in the monomer component and pre-formulated with additives, and finally formulated into a two-component system shortly before application. This process chain is relatively complex, and there is a great interest in simplifying it.

[0014] WO 2021 / 180488 first describes the production of methacrylate-based reactive resins for intumescent coatings using a slurry process. In this method, a monomer mixture is polymerized to a degree of polymerization of 70%, after which polymerization is terminated. The compositions described here are substantially similar to known reactive resins obtained by dissolving a suspended polymer or particles in a monomer mixture. The differences arise primarily from the nature of the polymer chains. Summary of the Invention

[0015] Purpose

[0016] The object of the present invention is therefore to provide a significantly simplified method for producing (meth)acrylate-based intumescent coatings.

[0017] In particular, a simplified manufacturing method is needed, in which at least one isolation or formulation step can be omitted compared to the methods for producing (meth)acrylate-based intumescent coatings described in the prior art.

[0018] A further objective is to provide a novel formulation for two-component intumescent coatings that, in addition to excellent metal adhesion and simple processability, allows for greater freedom in the addition of additives and the adjustment of subsequent foaming control, particularly regarding the preset of subsequent foam height and foam quality, such as a particularly high closed-cell foam fraction.

[0019] Further objectives not explicitly mentioned will be apparent from the following description or examples, as well as from the overall context of the invention.

[0020] Solution

[0021] These objectives are achieved by providing a novel method for producing reactive resins for intumescent coatings. In this method, a first monomer mixture containing at least one acid-functionalized monomer is first polymerized to a degree of polymerization of 70% to 95% by weight. Upon reaching the desired degree of polymerization, polymerization is then terminated. The resulting polymer, according to the invention, has a glass transition temperature calculated according to the Fox equation of less than 23°C, which is significantly lower than the glass transition temperatures reported in the prior art for the corresponding resins. Furthermore, the method of the invention is characterized in that, after polymerization termination, the mixture containing 70% to 95% by weight of the polymer is diluted with a second monomer mixture different from the first monomer mixture.

[0022] Existing foamed fire-retardant coatings are typically composed of multi-component systems, primarily formulated from thermoplastic polymers dissolved in monomers. However, this invention demonstrates that liquid polymers, i.e., polymers with a glass transition temperature below 23°C that are liquid in their undissolved state at room temperature, are also suitable for use. Furthermore, polymerized acid components, particularly 2-carboxyethyl acrylate, are used to improve adhesion to the substrate, while additional acid components added to the formulation, particularly acrylic acid or methacrylic acid, are used for unexpectedly effective control of foam height in its end use as a fire-retardant coating.

[0023] The Fox equation is a very simple yet realistic method for calculating the glass transition temperature of homogeneous copolymers (i.e., copolymers with a random distribution of repeating units), and it has proven particularly useful for (meth)acrylate copolymers (optionally containing styrene). The expression "(meth)acrylate" herein includes copolyacrylates, copoly-methacrylates, and copolymers comprising both acrylates and methacrylates. For two monomers, the Fox equation is shown below, and this can also be extended accordingly to a variety of different comonomers:

[0024] T g = T g1 (x1) + T g2 (x2)…+ T gy (x y )

[0025] in

[0026] T g Theoretical determination of glass transition temperature of copolymers

[0027] T gy Glass transition temperature of homopolymer of monomer y

[0028] x y The mass proportion of monomer y in a monomer mixture or a repeating unit in a polymer.

[0029] According to the present invention, the data listed for all glass transition temperatures pertain to polymers produced by free radical processes at polymerization temperatures commonly ranging from 40 to 120 °C. Exotisch polymers produced at significantly lower temperatures, such as by anionic polymerization or by stereoselective GTP polymerization, are not applicable in the present invention. For these polymers, the Fox equation is also not applicable in its chosen form due to the very different stereoregularities. The glass transition temperatures of homopolymers produced by free radical polymerization are known in the literature.

[0030] In this invention, monomer mixtures are generally understood to refer to solvent-free monomer mixtures. More specifically, for the purposes of this invention, monomer mixtures are free of any water. Monomer mixtures are therefore preferably mixtures composed of monomers. These interpretations and preferences apply independently to both the first monomer mixture and the second monomer mixture.

[0031] The first monomer mixture preferably consists of acrylates and / or methacrylates in at least 90% by weight based on the total weight of the first monomer mixture. Also preferably, the acid-functionalized monomers in the first monomer mixture are acrylic acid, methacrylic acid, itaconic acid, and / or 2-carboxyethyl acrylate, more preferably methacrylic acid and / or 2-carboxyethyl acrylate. Furthermore, the first monomer mixture preferably contains, in addition to the acid-functionalized monomers, methyl (meth)acrylate (MMA), n-butyl (meth)acrylate, isobutyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, ethylhexyl (meth)acrylate, and / or styrene as additional monomers. The first monomer mixture is particularly preferably, and very particularly preferably, consists entirely of the monomers listed herein in at least 95% by weight based on the total weight of the first monomer mixture.

[0032] The monomer mixture herein particularly preferably contains 20% to 45% by weight, more preferably 25% to 40% by weight, of methacrylates, especially, for example, ethylhexyl methacrylate. Preferably, a maximum of 10% by weight of acid-functionalized monomers is used in the monomer mixture, in each case based on the total weight of the first monomer mixture.

[0033] In one embodiment of the invention, the first monomer mixture is styrene-free. Therefore, the first monomer mixture is preferably styrene-free.

[0034] Further preferably, the first monomer mixture, in the form of acrylates and / or methacrylates, is free of crosslinking agents. Particularly preferably, the first monomer mixture is free of crosslinking agents.

[0035] In this invention, "crosslinking agent" is understood to mean a monomer containing two or more functional groups that can be polymerized in the polymerization according to the invention, especially in free radical polymerization.

[0036] The degree of polymerization at the termination of the polymerization is preferably between 85% and 95% by weight. Particularly preferably, the polymer formed from the first monomer mixture according to the invention contains repeating units of acid-functionalized monomers at 1% to 10% by weight, preferably 2.5% to 5% by weight, based on the total weight of the polymer formed. More preferably, the formed polymer has a weight-average molecular weight M between 10,000 and 200,000 g / mol, preferably between 20,000 and 150,000 g / mol, and more preferably between 30,000 and 100,000 g / mol. w It has a glass transition temperature between -20°C and 20°C, preferably between -5°C and 15°C.

[0037] Here, the glass transition temperature data listed also refer to values ​​preset using the Fox equation. The final actual glass transition temperature can be determined after polymerization, for example, by DSC (differential scanning calorimetry, e.g., according to ISO 11357-1, particularly ISO 11357-2). When using the monomers described above, the values ​​determined by this method typically differ only slightly from the values ​​preset using the Fox equation. If other monomers are used, this can, in very rare cases, result in a blocky distribution of repeating units in the chain. In very rare cases, block formation may be so significant that the polymer has two or more glass transition temperatures. For these very rare, unpreferred cases according to the invention, calculating the glass transition temperature using the Fox equation is no longer decisive; instead, the most significant glass transition temperature is determined according to the aforementioned standard ISO 11357-2.

[0038] Here, the weight-average molecular weight was determined by GPC using at least two suitable columns with THF as the eluent and PMMA standard as the reference.

[0039] It has been surprisingly found that the polymers formed in the method of the present invention have glass transition temperatures below ambient room temperature, meaning they are liquids even at room temperature and in the separated state.

[0040] The polymerization can be carried out discontinuously, particularly in a batch process, or continuously in a stirred tank reactor with connected flow tubes. Termination of the reaction can be performed substantially independently of the operating mode, but in each case it can be adapted by lowering the temperature, adding inhibitors, and / or simply by consuming the initiator.

[0041] Preferably, the second monomer mixture comprises 50% to 90% by weight, more preferably 75% to 85% by weight, of methyl methacrylate (MMA) based on the total weight of the second monomer mixture. More preferably, the second monomer mixture contains at least 90% by weight of acrylates and / or methacrylates and optionally styrene, preferably MMA, n-butyl methacrylate, isobutyl methacrylate, ethyl methacrylate, propyl methacrylate and / or ethylhexyl methacrylate, up to 5% by weight of acid-functionalized monomers, preferably acrylic acid, methacrylic acid, itaconic acid and / or 2-carboxyethyl acrylate, and optionally up to 5% by weight of styrene, in each case based on the total weight of the second monomer mixture.

[0042] In an alternative preferred embodiment of the invention, the second monomer mixture contains 55% to 80% by weight, more preferably 60% to 75% by weight, of methacrylate, in each case based on the total weight of the second monomer mixture, wherein methyl methacrylate and n-butyl methacrylate are used, for example, in a ratio of about 80% by weight: 20% by weight to 50% by weight: 50% by weight.

[0043] In one embodiment, the second monomer mixture has an acid-functionalized monomer in the range of 0.5% to 2% by weight based on the total weight of the second monomer mixture.

[0044] In this invention, "acid-functional monomer" is understood to refer to exactly one acid-functional monomer or a mixture of two or more acid-functional monomers.

[0045] Further preferably, the second monomer mixture is styrene-free. The second monomer mixture is therefore preferably styrene-free. Particularly preferably, the reactive resin is styrene-free.

[0046] Further preferably, the second monomer mixture is free of crosslinking agents. Particularly preferably, the reactive resin is free of crosslinking agents. The interpretation and preferences described above apply to the term "crosslinking agent".

[0047] Particularly preferably, the second monomer mixture is selected such that, upon complete polymerization, it yields a polymer having a glass transition temperature according to the Fox equation between 50°C and 120°C, preferably between 60°C and 90°C. It should be clear at this point that the polymer in the finished intumescent coating, formed primarily of these monomers from the second monomer mixture, will in most cases deviate from the theoretical glass transition temperature of the second monomer mixture calculated using the Fox equation, because this second polymerization occurs during the curing process of a mixture based on the second monomer mixture and a maximum of 30% by weight of the remaining first monomer mixture (different from the second monomer mixture) relative to the total weight of the reactive resin.

[0048] In addition to the method of the present invention, the present invention also provides novel formulations for two-component intumescent coatings. These formulations are characterized in that, at a time point after mixing the two-component system, they contain 20% to 40% by weight of a reactive resin prepared by the method of the present invention, 35% to 60% by weight of a foaming agent, 0.1% to 2.5% by weight of a peroxide and / or an azo initiator, preferably only a peroxide, such as benzoyl peroxide, optionally up to 2% by weight of an accelerator, optionally 4.9% to 15% by weight of an additive, and 5% to 30% by weight of a filler. Optionally, the formulation may include additional pigments, in each case based on the total weight of the two-component system.

[0049] Additives may include, in particular, wetting agents, film-forming agents, degassing agents, and / or dispersing agents. Accelerators, which may be used optionally, are typically secondary amines.

[0050] Fillers can be, for example, silica, titanium dioxide, quartz, or other particularly thermally stable inorganic compounds. Thermally decomposable inorganic fillers such as carbonates are permitted only in limited quantities to avoid uncontrolled additional foaming of the coating in the event of a fire. Titanium dioxide is a particularly preferred filler.

[0051] Various alternatives exist regarding foaming agents. In a particularly preferred alternative, a polyphosphate can be used, which is converted to phosphoric acid at 190 to 300°C. The formulation also includes pentaerythritol, which subsequently forms carbon foam upon dissociation of water and carbon dioxide in the presence of phosphoric acid at temperatures above 300°C. In this approach, water and carbon dioxide act as foaming agents. An additional advantage of this alternative is that both the polyphosphate and phosphoric acid act as additional flame retardants.

[0052] In the second alternative, melamine is used as the base material for the foaming agent. It decomposes into ammonia, nitrogen and carbon dioxide at temperatures above 350°C, all of which act as foaming agents.

[0053] The combination of these two alternatives forms a third, particularly preferred variant, enabling further advantages beyond flame retardancy. In this way, the degree of foaming can be more precisely controlled. Furthermore, the gradual foaming process provides advantages in terms of foam stability.

[0054] When polyphosphate and melamine are surprisingly mixed in parallel with the reactive resin according to the invention at a ratio between 3:1 and 1:1, for example 2:1, foams with particularly fine pores and closed pores are obtained.

[0055] Initiators typically consist of one or more peroxide and / or azo initiators, preferably peroxides. They can be used together with accelerators, typically one or more tertiary amines, especially aromatic tertiary amines, as an initiator system. A particularly suitable example of such an initiator is benzoyl peroxide, which can also be used, for example, in the form of a safe pre-formulated paste, wherein the auxiliary agents contained in the paste, such as paraffin, do not interfere with the formulation at appropriate concentrations.

[0056] Examples of accelerators include N,N-dialkyl-p-toluidines, such as N,N-bis(2-hydroxypropyl)-p-toluidine, N,N-dimethyl-p-toluidine, or N,N-dimethylaniline.

[0057] The actual coating composition can be formulated as follows: A reactive resin is formulated together with a foaming agent, additives, optional fillers, and other optional fillers. These intermediate formulations are then separated into, for example, two fractions of equal size. One of these fractions is then separately mixed with an accelerator. Both fractions are subsequently stored stably for an extended period.

[0058] Before actual application, the fraction without the accelerator is then mixed with the initiator or an initiator mixture. After prolonged storage or transportation, both fractions may need to be stirred again, as fillers may have settled, for example. After the initiator is added or otherwise incorporated, the two fractions of the two-component system are then mixed together. This initiates the polymerization of the monomeric components of the reactive resin, which is the start of the so-called pot life, within which the resin must be applied to the substrate, i.e., for example, to a steel beam. For modern coating equipment, the mixing of the two fractions of the two-component system can also be carried out in the mixing chamber of the coating nozzle just before pressure-indicating spraying.

[0059] The pot life is determined by the combination of the properties and concentrations of the initiator and accelerator, the monomer mixture, and external influencing factors such as ambient temperature. These factors can be readily assessed and adjusted by those skilled in the art. A pot life is typically defined as a period from a few minutes to a few hours; however, it can also be marked as exceeding 20 hours.

[0060] The present invention also provides a method for coating a metal surface with an intumescent coating. In this method, the above-described formulation for a two-component intumescent coating is prepared, applied to the metal surface within 1 to 20 minutes, and cured there at a temperature between -5 and 30°C, preferably between 0 and 30°C, for 60 minutes. The preferred thickness of the unfoamed coating is 1 to 20 mm, more preferably 1.5 to 7.5 mm. It is formulated such that, in the event of a fire, the coating preferably results in a foaming ratio of 5 to 100 mm / mm, preferably 15 to 50 mm / mm. Detailed Implementation

[0061] Example

[0062] Example 1

[0063] Monomer feeding method:

[0064] A first monomer mixture for polymer fractionation, consisting of 23 wt% MMA, 33 wt% ethylhexyl methacrylate, 36 wt% n-butyl methacrylate, and 8 wt% β-CEA (2-carboxyethyl acrylate), was mixed at room temperature with 1 wt% 2-ethylhexyl mercaptoacetate and 0.6 wt% di(4-tert-butylcyclohexyl) peroxydicarbonate or 2,2'-azobis(isobutyronitrile) to achieve a target molecular weight of approximately 60,000 g / mol. 25% of the first monomer mixture was heated to 74°C with stirring as a pre-batch. Heating was stopped, and the mixture was allowed to autothermally polymerize at approximately 90 to 149°C by continuously adding the remaining 75 wt% of the first monomer mixture at 86°C. The process was terminated after approximately 30 to 60 minutes of metered addition. After a further reaction time of approximately 45 minutes, a second monomer mixture consisting of 79 wt% methyl methacrylate, 20 wt% ethylhexyl acrylate, and 1 wt% methacrylic acid was added to the batch at a ratio of 30 wt% polymer fraction to 70 wt% monomer mixture for dilution. The batch was cooled to 30°C and stabilized with 15 ppm (15 mg / kg) 2,6-di-tert-butyl-4-methylphenol (Topanol O), and formulated with 1.2 wt% wax (dropping point approximately 60°C) and 1.9 wt% N,N-bis(2-hydroxypropyl)-p-toluidine.

[0065] Viscosity was determined at 20°C using a DIN cup 4 with a flow time of 30 s, corresponding to 30-150 mPa*s. The target polymer content was approximately 30-35%. The resulting polymer had a glass transition temperature of approximately -5°C and was not crosslinked.

[0066] Example 2

[0067] Initiator feeding method

[0068] A first monomer mixture for the polymer fraction, consisting of 23 wt% MMA, 33 wt% ethylhexyl methacrylate, 36 wt% n-butyl methacrylate, and 8 wt% β-CEA (2-carboxyethyl acrylate), was mixed with approximately 2 wt% 2-ethylhexyl mercaptoacetate at room temperature. The first monomer mixture was heated to 74°C with stirring, heating was stopped, and the mixture was autothermally polymerized at approximately 90 to 120°C at 86°C by continuously adding 0.6 wt% of di(4-tert-butylcyclohexyl) peroxydicarbonate or 2,2'-azobis(isobutyronitrile) as a 10 wt% solution in n-butyl acetate, to achieve a target molecular weight of approximately 60,000 g / mol. The process was terminated after a metered addition time of approximately 60 to 120 minutes. After a further reaction time of approximately 45 minutes, a second monomer mixture consisting of 79 wt% methyl methacrylate, 20 wt% ethylhexyl acrylate, and 1 wt% methacrylic acid was added to the batch at a ratio of 30 wt% polymer fraction to 70 wt% monomer mixture for dilution. The batch was cooled to 30°C and stabilized with 15 ppm (15 mg / kg) 2,6-di-tert-butyl-4-methylphenol (Topanol O), and formulated with 1.2 wt% wax (dropping point approximately 60°C) and 1.9 wt% N,N-bis(2-hydroxypropyl)-p-toluidine.

[0069] Viscosity was determined at 20°C using a DIN cup 4 with a flow time of 30 s, corresponding to 30-150 mPa*s. The target polymer content was approximately 30-35%. The resulting polymer had a glass transition temperature of approximately -5°C and was not crosslinked.

[0070] Comparative Example 1:

[0071] 1710 and 1720 were mixed in equal parts.

[0072] Curing of resin systems:

[0073] Based on 2% by weight of benzoyl peroxide in the resin mixture

[0074] Comparative Example 1:

[0075] Applicable period: 18 minutes

[0076] Tmax: 85℃ after 34 minutes; Target: 70-130℃ after 15-40 minutes.

[0077] Glass transition temperature: 64℃

[0078] Example 1:

[0079] Applicable period: 18 minutes

[0080] Tmax: 90℃ after 42 minutes; Target: 70-130℃ after 15-40 minutes.

[0081] Glass transition temperatures: approximately -5°C and approximately 74°C

[0082] The lower glass transition temperature here refers to the polymer from the partial polymerization of the first monomer mixture, while the higher glass transition temperature refers to the polymer formed during the final curing process of the coating.

[0083] Formulation of fire-retardant coatings

[0084] Application Examples:

[0085] 33.8 wt% of the reactive resin according to Example 1 and Comparative Example 1 was pre-formulated in each case with 30.0 wt% ammonium phosphate, 9.2 wt% pentaerythritol, 15.0 wt% melamine, 10.0 wt% titanium dioxide, and 1 wt% kaolin and a wetting agent. These formulations were then each divided into two equal fractions, with 0.5 wt% benzoyl peroxide added to one fraction based on the total formulation. The two fractions were then mixed together, and the smaller fraction was collected. The larger fraction was used to coat steel sheets with a layer thickness of 2000 μm, while the smaller sample, after mixing, was used to measure the pot life and maximum temperature.

[0086] Foaming experiment

[0087] Experiments in a High Therm VMK 39 muffle furnace

[0088] The pre-initiated resin-filler system was applied to a degreased 0.8 mm thick steel plate using a 3000 μm doctor blade. After curing for 24 hours, the coated plate was placed in a cold muffle oven and heated to the desired temperature. After reaching the temperature, it was held for 1 hour, and then the oven was allowed to cool.

[0089] Evaluation of thermally foamed intumescent coatings, including specific foam height, foam quality, and adhesion to steel plates.

[0090]

[0091] The results of Examples 1 and 2 show higher specific foam heights, which therefore enable them to provide better fireproof insulation.

Claims

1. A method for producing a reactive resin for use in intumescent coatings, characterized in that... A first monomer mixture containing at least one acidic functional monomer is polymerized until a degree of polymerization of 70% to 95% by weight is reached, after which polymerization is terminated. The resulting polymer has a glass transition temperature of less than 23°C calculated according to the Fox equation. After polymerization is terminated, a mixture containing 70% to 95% by weight of the polymer is diluted with a second monomer mixture different from the first monomer mixture. The first monomer mixture consists of acrylates and / or methacrylates in an amount of at least 90% by weight. The acid-functionalized monomers in the first monomer mixture are acrylic acid, methacrylic acid, itaconic acid, and / or 2-carboxyethyl acrylate. The second monomer mixture contains at least 90% by weight of acrylates and / or methacrylates, up to 5% by weight of acid-functionalized monomers, and optionally styrene, in each case based on the total weight of the second monomer mixture.

2. The method according to claim 1, characterized in that... The acid-functional monomers in the first monomer mixture are methacrylic acid and / or 2-carboxyethyl acrylate.

3. The method according to claim 2, characterized in that... The polymer formed contains repeating units of acid-functional monomers at a weight percentage of 1% to 10% based on the total weight of the polymer formed.

4. The method according to any one of claims 1 to 3, characterized in that... The first monomer mixture consists of an acid-functionalized monomer and an additional monomer selected from MMA, n-butyl methacrylate, isobutyl methacrylate, ethyl methacrylate, propyl methacrylate, ethylhexyl methacrylate, and / or styrene.

5. The method according to any one of claims 1 to 3, characterized in that... The resulting polymer has a weight-average molecular weight M in the range of 10,000 to 200,000 g / mol. w And the glass transition temperature between -20°C and 20°C.

6. The method according to any one of claims 1 to 3, characterized in that... The polymerization is carried out discontinuously in a batch process or continuously in a stirred tank reactor with connected flow tubes, wherein the reaction is terminated by reducing the temperature, adding an inhibitor, and / or by consuming an initiator.

7. The method according to any one of claims 1 to 3, characterized in that... The degree of polymerization at the end of polymerization is between 85% and 95% by weight.

8. The method according to any one of claims 1 to 3, characterized in that... The second monomer mixture contains MMA, n-butyl methacrylate, isobutyl methacrylate, ethyl methacrylate, propyl methacrylate and / or ethylhexyl methacrylate, and acrylic acid, methacrylic acid, itaconic acid and / or 2-carboxyethyl acrylate as acid functional monomers.

9. The method according to any one of claims 1 to 3, characterized in that... The second monomer mixture is selected so that, upon complete polymerization, it yields a polymer with a glass transition temperature between 50°C and 120°C according to the Fox equation.

10. A formulation for use in two-component intumescent coatings, characterized in that, After mixing the two-component system, the formulation contains 20% to 40% by weight of a reactive resin prepared by the method according to any one of claims 1 to 9, 35% to 60% by weight of a foaming agent, 0.1% to 2.5% by weight of a peroxide and / or azo initiator, optionally up to 2% by weight of an accelerator, optionally 4.9% to 15% by weight of an additive, and 5% to 30% by weight of a filler, in each case based on the total weight of the two-component system.

11. A formulation for use in two-component intumescent coatings, characterized in that, After mixing a two-component system of reactive resin prepared according to any one of claims 1 to 9, the formulation has a foaming agent ratio of polyphosphate to melamine between 1:1 and 3:

1.

12. The formulation according to claim 11, characterized in that... The formulation also contains pigments.

13. A method for coating a metal surface with an intumescent coating, characterized in that... The formulation prepared according to claim 10 or 11 is applied to a metal surface within 1 to 20 minutes and cured there at a temperature between -5 and 30°C for 60 minutes.

Citation Information

Patent Citations

  • Flame-retardant, waterproof water-based core-shell acrylate resin coating and preparation method of paint

    CA3028431A1

  • Acrylic polymer emulsion for ultrathin intumescent fire-retardant coating and preparation method thereof

    CN111995919A

  • Ultrathin intumescent fireproof coating

    CN112029367A

  • interior fittings for rail vehicles

    DE19630063A1

  • Intumescent coating compositions

    EP1636318A1